Sigesbeckia pubescens makino alleviates ulcerative colitis in mice by modulating the Nrf2/Keap1 pathway - Qiu-Shuo Ma; Qi-Ling Chen; Guo-Ping Wu; Ya-Wen Yao; Yu-Xin Fan; Ke-Gang Linghu; Jun-Ming Chen; Wei Xiong; Hua Yu; Hua Yu (Frontiers in Pharmacology)
BackgroundUlcerative colitis (UC) is a prevalent immune-mediated inflammatory bowel disease characterized by mucus secretion, hematochezia, and diarrhea. This study compared the therapeutic effects of three Siegesbeckiae Herba (SH) species used in traditional Chinese medicine—Sigesbeckia orientalis L (SO), Sigesbeckia pubescens Makino (SP), and Sigesbeckia glabrescens Makino (SG) — in dextran sulfate sodium (DSS)-induced UC mice.MethodsUC was induced in C57BL/6 mice with 3% DSS for 7 days. Cytokine levels in serum and colon tissues were measured by enzyme-linked immunosorbent assay. Protein and gene expression were analyzed using Western blotting and PCR. Histopathological changes were assessed via hematoxylin-eosin staining, immunohistochemistry, and immunofluorescence. Fecal specimens were collected for gut microbiota analysis. An in vitro UC model was also established in NCM460 cells using lipopolysaccharide (LPS), and Caco-2 cells were used to examine intestinal mucosal integrity.ResultsSP substantially decreased the disease activity index, enhanced colon shortening, and mitigated histological damage in comparison to the model group. Mechanistic investigations demonstrated that SP functioned via the activation of the Nrf2/Keap1 pathway, markedly increased the activity of the antioxidant enzyme glutathione in colon tissues, decreased the concentration of the oxidative marker malondialdehyde, and upregulated the expression of the downstream genes H O -1 and NQO1.ConclusionThe study reveals for the first time the differences in efficacy of different species of SH and its molecular mechanism, demonstrating that SP increases oxidative defense via the activation of the Nrf2/Keap1 pathway, therefore mitigating colitis and oxidative damage in UC mice. This discovery not only establishes a scientific foundation for the selective preference of SH species but also offers a novel technique for the creation of natural pharmaceuticals aimed at the Nrf2 pathway for the treatment of UC.